Pengembangan Aplikasi Media Pembelajaran untuk Meningkatkan Minat Belajar Matematika - Muhammad Hafidh Ma'ruf; Wahidin Wahidin (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
This research aims to see whether the AritGeo application can be used as a learning tool and can increase students' interest in mathematics. The research method used is the RD (Research and Development) development method, which includes (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product trials, and (7) product revisions, as modified from the Borg Gall development model. The participants in this study were 30 class VIII students of SMP Muhammadiyah 1 Jakarta. The materials included in the application were arithmetic and geometry. The AritGeo application got good test results. The 3 in one concept between materials, exercises, and music can increase students' interest in learning. The results of material expert validation obtained an average percentage of 80.83%, media expert validation results of 90.05%, and student satisfaction test results of 82%. This value illustrates that the AritGeo application is in the excellent category